Analysis of Work Environment and Work Stress on Work Productivity PT. MSM - Togar Naibaho; Winfrontstein Naibaho (Enrichment : Journal of Management, 2022)
The purpose of this study was to determine the effect the work environment and work stress on work productivity at PT.MSM either partially or simultaneously. The method used is descriptive explorative. The population in this study were all employees who totaled 40 people at PT.MSM Medan. Because the total population of less than 100 people, the number of samples taken throughout the population (saturated sample) as many as 40 people. Data analysis techniques using multiple linear regression analysis, the determinant test, F test and t test. Results of the study resulted in an equation an equation: Prod= 2,092 + 0,965LinKER - 0,433Stres. Test Results Adjusted R Square obtained a value of 0.963, this figure illustrates that the variation of the rise and fall of labor productivity variable value of 96,3% is determined by the work environment variables and work stress while the remaining3,7% is influenced by variables that did not participate in the research study such as compensation, motivation and others. Simultaneously working environment and work stress were significant effect on work productivity at PT.MSM Medan, is evident from the test results simultaneously obtained value of F (548,07) with a significant level of 0.00 is smaller than alpha (0.05). Partially, the working environment have a significant effect on work productivity at PT.MSM Medan, where the partial results obtained for the work environment variable is 31,966 with significance level (0.000) is smaller than 0.05, while work stress has significant effect too on productivity known work of the partial test results obtained yield was -8,646 with significance level (0.000) smaller than 0.05.